CLINICAL FEATURES OF PATIENTS WITH ACL TEARS AND RELATED KNEE MRI RESULTS AT DR. SAIFUL ANWAR HOSPITAL (Department of Radiology, Medical Faculty, University of Brawijaya, 2025)
The most frequent injury to the knee is an anterior cruciate ligament (ACL) tear. MRI is a highly accurate method for diagnosing ACL injuries. Research on injuries associated with ACL tears in Malang City is still relatively limited, which is why it is necessary to conduct research at Dr. Saiful Anwar Hospital. A descriptive observational study was conducted over a one-year period. Patients with ACL damage, as documented in the Radiology Information System at the time of the MRI examination, made up the study population. We examined information from ACL tear cases in the Radiology Department as well as injuries to the posterior cruciate ligament (PCL), medial meniscus, lateral meniscus, medial collateral ligament (MCL), and lateral collateral ligament (LCL). We discovered that, of the 58 ACL tear patients, 83% were male and 17% were female. At 44.8%, the frequency was highest among those aged 21 to 30. Interestingly, 81% of participants had a partial ACL injury and 19% had a total ACL tear. The PCL (29%), the LCL (15.5%), the MCL (13.8%), the medial meniscus (56.2%), and the lateral meniscus (51.7%) are the most commonly associated injuries with ACL tears. Males in this group who are young and physically active are more likely to suffer from ACL tears. Due to the biomechanical connection between the ACL and menisci, meniscus injuries are the most common concomitant injuries observed in patients with ACL rupture.